503 NATURALLY OCCURRING LEUKOPENIA AS A MARKER FOR GOOD OUTCOME AFTER CARDIAC TRANSPLANTATION. Issue 1 (1st January 2007) - Song, H.; Kittleson, M. M.; Yajnik, M.; Wu, G. W.; Kobashigawa, B. I.; Patel, J. K.; Hamilton, M. A.; Kobashigawa, J. A.
Abstract : Purpose: The mechanisms of graft tolerance are not well understood. It appears that a regulatory or an immune suppression mechanism is responsible for this process. In our institution we have noticed an improved outcome for patients with naturally occurring leukopenia. Methods: We reviewed 839 patients who received a heart transplant between 1984 and 2001. Leukopenia was defined as WBC < 4, 000 at 6 months or greater post-transplant despite elimination of all myelosuppressive agents and persisting for at least 3 months. Patients with concomitant viral syndromes (cytomegalovirus) or other extrinsic causes for leukopenia were excluded. Five-year outcomes data were recorded for all patients. Results: Eighteen patients with leukopenia were compared with 821 patients without leukopenia (control). Seventeen of 18 leukopenic patients were initiated on cyclosporine, azathioprine, and corticosteroids. One patient was initiated on tacrolimus and MMF/corticosteroids. Five-year survival was 94% in the leukopenia group and 68% in the control group ( p = .01; see Figure ). Moreover, the leukopenia group exhibited a trend toward increased freedom from cardiac allograft vasculopathy (CAV) compared with control (83% vs 67%, p = .11). First-year rejection and infection incidence and demographic characteristics, including recipient and donor age, percent female, ischemic time, and number of HLA mismatches, were not different between the two groups. Conclusions: Naturally occurring leukopenia more than 6 months after transplant in heart transplant patients appears to be associated with graft tolerance by improved graft survival and freedom from CAV. Further investigation into the mechanism of the beneficial effect of leukopenia is warranted.